Influence of Nanoparticles and Drop Size Distributions on the Rheology of w/o Pickering Emulsions1. Issue 11 (16th September 2016) - Hohl, Lena; Röhl, Susanne; Stehl, Dmitrij; von Klitzing, Regine; Kraume, Matthias
Abstract: The rheological behavior of particle/oil suspensions and w/o Pickering emulsions consisting of water, 1‐dodecene and different fumed silica nanoparticles was investigated. The particles varied in hydrophobicity and specific surface area. The influence of particle concentration and water content on rheology was determined and the emulsion drop size distributions were examined. Emulsions with different drop sizes were created by either varying the particle concentration or the water content. It was found that the particles in the continuous oil phase and not the drop size distribution seem to be the major influencing factor on the Pickering emulsion rheology. Abstract : The rheology of particle/oil suspensions and w/o Pickering emulsions consisting of water, 1‐dodecene and silica nanoparticles was investigated. The influence of particle concentration and water content on rheology and drop sizes was determined. Residual particles in the oil phase seem to be the major influencing factor on the emulsion rheology.